Differences in Brain Structure and Function Among Yoga Practitioners and Controls - Gothe, Neha P.; Hayes, Jessica M.; Temali, Cindy; Damoiseaux, Jessica S. (Frontiers in Integrative Neuroscience, 2018)
Background: Yoga is a mind-body based physical activity that has demonstrated a variety of physiological, psychological and cognitive health benefits. Although yoga practice has shown to improve cognitive performance, few studies have examined the underlying neurological correlates. Objective: The current study aimed to determine the differences in gray matter volume of the hippocampus, thalamus, and caudate nucleus and brain activation during the Sternberg working memory task. Method: Participants were 13 experienced yoga practitioners (mean age=35.8), defined as having more than 3 years of regular yoga practice, and 13 age- and sex-matched controls (mean age=35.7). All participants completed a 6-minute walk test to assess fitness, psychosocial and demographic questionnaires; and underwent magnetic resonance imaging to assess gray matter volume and brain activation. Results: There were no group differences on demographic measures of income, education, and on estimated VO2max or physical activity levels. Gray matter volume differences were observed in the left hippocampus, showing greater volume in experienced yoga practitioners compared to controls (p = .017). The functional MRI results revealed less activation in the dorsolateral prefrontal cortex in yoga practitioners compared to controls during the encoding phase of the Sternberg task (p < .05). Reaction time and accuracy on the task did not differ between the groups. Conclusions: Our results suggest an association between regular long-term yoga practice and differential structure and function of specific brain regions involved in executive function, specifically working memory, which has previously shown to improve with yoga practice. Future studies need to examine intervention effects of yoga and explore its potential to maintain and improve cognitive health across the lifespan through longitudinal and intervention studies.